2022
DOI: 10.1371/journal.pone.0266845
|View full text |Cite
|
Sign up to set email alerts
|

Development of Duchenne Video Assessment scorecards to evaluate ease of movement among those with Duchenne muscular dystrophy

Abstract: Background Patients with Duchenne muscular dystrophy (DMD) adopt compensatory movement patterns as muscles weaken. The Duchenne Video Assessment (DVA) measures patient ease of movement through identification of compensatory movement patterns. The DVA directs caregivers to video record patients performing specific movement tasks at home using a secure mobile application, and DVA-certified physical therapists (PTs) score the videos using scorecards with prespecified compensatory movement criteria. The goal of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Individual clinician feedback was first gathered without the influence of other clinicians, then through sharing perspectives in focus groups to guide critical item and scale changes. This 2-step process of gathering and assimilating expert clinician feedback on the scale informed by previous scale development work by Contesse et al 35 is an additional strength of this study. We found that expert clinicians corroborated caregiver perceptions of clinically meaningful health-related functions in infantile GM2.…”
Section: Discussionmentioning
confidence: 96%
“…Individual clinician feedback was first gathered without the influence of other clinicians, then through sharing perspectives in focus groups to guide critical item and scale changes. This 2-step process of gathering and assimilating expert clinician feedback on the scale informed by previous scale development work by Contesse et al 35 is an additional strength of this study. We found that expert clinicians corroborated caregiver perceptions of clinically meaningful health-related functions in infantile GM2.…”
Section: Discussionmentioning
confidence: 96%
“…The COVID-19 pandemic highlighted the need for clinical outcome assessments that can be administered remotely (Goldsack After the DVA movement tasks were finalized, a modified Delphi process was conducted with experts to identify and modify the movement compensations to include on the scorecards (Contesse et al, 2022). The DVA has been found to have high inter-and intrarater reliability, and cross-sectional construct validity has been established (Contesse et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Data monitors review videos to ensure standardized data quality parameters are met, and caregivers are asked to re‐record videos that would not be able to be scored by a physical therapist. DVA‐certified physical therapists score the videos using scorecards (example provided in Figure 1) with prespecified compensatory movement criteria (Contesse et al., 2022). The DVA can evaluate patients with DMD at any point in their disease progression, and patients are assigned movement tasks based on functional status.…”
Section: Introductionmentioning
confidence: 99%